2020
DOI: 10.1021/acs.analchem.0c00187
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Interface: Efficient Extraction of Magnetic Beads from Nanoliter Droplets for Automated Sequential Immunoassays

Abstract: Droplet-based microfluidic systems offer a high potential for miniaturization and automation. Therefore, they are becoming an increasingly important tool in analytical chemistry, biosciences, and medicine. Heterogeneous assays commonly utilize magnetic beads as a solid phase. However, the sensitivity of state of the art microfluidic systems is limited by the high bead concentrations required for efficient extraction across the water–oil interface. Furthermore, current systems suffer from a lack of technical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The use of cross-linking technology based on such preformed polymers has an advantage over the often-described polymerization reactions in liquid droplet based microfluidic environments in that no monomer is involved, which allows performance of the reactions outside a chemical laboratory. 6,17,29 Shape-Based and Optical Barcoding of Hydrogel Beads. Barcodes provide information about an object in a machine-readable layout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cross-linking technology based on such preformed polymers has an advantage over the often-described polymerization reactions in liquid droplet based microfluidic environments in that no monomer is involved, which allows performance of the reactions outside a chemical laboratory. 6,17,29 Shape-Based and Optical Barcoding of Hydrogel Beads. Barcodes provide information about an object in a machine-readable layout.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of Superparamagnetic and ID Particles into the Beads. Magnetic particles are used in many heterogeneous assays 29,32 as they allow simplified collection and washing of the beads by applying an external magnetic field. 33 Also for the incorporation of magnetic particles, the photo-cross-linking process provides an optimal platform.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the microfluidic droplet technology we used allows for homogeneous and stable droplets to be generated within reaction chambers at high throughputs. Lastly, microfluidic immunoassay technology also provides high sensitivity, low sample size, and high throughput over flow cytometry and microplate readers, making it an increasingly popular choice for analysis research [28, 3843].…”
Section: Discussionmentioning
confidence: 99%
“…These on-chip sample transfers can be executed by droplet microfluidics. Metzler et al [86] reported an automated microfluidic immunoassay enables target capture, labeling, magnetic preconcentration, and fluorescence detection sequentially processed in microdroplet flow. In their microchip device, two auxiliary channels were connected to the main analysis channel via T-junctions to merge droplets containing antibody-coated magnetic beads with the sample as well as fluorophorelabeled detection antibodies sequentially, and two external magnets were placed downstream of the main analysis channel to accumulate magnetic sandwiched immunocomplexes for fluorescence detection.…”
Section: Lab-on-a-chip Sample Preparation Techniquesmentioning
confidence: 99%